2020
DOI: 10.3390/app10020541
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Security of Pattern Unlock with Surface EMG-Based Biometrics

Abstract: Pattern unlock is a popular screen unlock scheme that protects the sensitive data and information stored in mobile devices from unauthorized access. However, it is also susceptible to various attacks, including guessing attacks, shoulder surfing attacks, smudge attacks, and side-channel attacks, which can achieve a high success rate in breaking the patterns. In this paper, we propose a new two-factor screen unlock scheme that incorporates surface electromyography (sEMG)-based biometrics with patterns for user … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…However, it has been shown that for a short time contraction, the sEMG signals satisfy the stationary assumptions [31]. Therefore, for a short duration, isometric contractions suitable for biometric applications [10][11][12], the time domain and frequency domain features are ideal for feature extraction as their mean and variances have minimal variations [32]. These include Hudgin's time-domain (TD) feature set [24] and two frequency domain feature sets: Frequency division technique (FDT) [21,26] and Autoregressive coefficients (AR) [27,33].…”
Section: A Feature Extraction Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it has been shown that for a short time contraction, the sEMG signals satisfy the stationary assumptions [31]. Therefore, for a short duration, isometric contractions suitable for biometric applications [10][11][12], the time domain and frequency domain features are ideal for feature extraction as their mean and variances have minimal variations [32]. These include Hudgin's time-domain (TD) feature set [24] and two frequency domain feature sets: Frequency division technique (FDT) [21,26] and Autoregressive coefficients (AR) [27,33].…”
Section: A Feature Extraction Methodsmentioning
confidence: 99%
“…It is likely that they will find applications in low-risk authentication scenarios, complementary to other well-established biometric modalities. Although multiple studies have investigated EEG and ECG as a biometric trait, there have been limited studies that use surface electromyogram (sEMG) from the forearm and hand muscles while performing hand gestures [6,[10][11][12]. Due to the characteristic property that different movements result in distinctive EMG patterns, sEMG has been predominantly used for accurate hand gesture recognition [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the EMG-based authentication systems are more suitable because they are not influenced by the surrounding noise or the health of the user. Therefore, authentication studies using EMG signals have been actively conducted in the recent years [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, the EMG signal was used to unlock the pattern lock by drawing a pattern after attaching a wet electrode to the forearm, and data were classified using a oneclass classification algorithm [13]. These previously proposed methods are inconvenient owing to the following reasons: The size of the motion must be large, and the sample signal must be set for each person.…”
Section: Introductionmentioning
confidence: 99%